Clinical and Biochemical Evaluation of Lozenges Containing Lactobacillus reuteri as an Adjunct to Non-Surgical Periodontal Therapy in Chronic Periodontitis - ALTURFAN, EBRU IŞIK (WILEY, 2015)
Background: This study evaluates the effects on clinical and biochemical parameters of Lactobacillus reuteri-containing probiotic supplementation adjunctive to initial periodontal therapy in patients with chronic periodontitis (CP). Methods: Thirty patients with CP were included and divided into two groups. Every patient had, in each quadrant, >= 2 teeth each with approximal sites with a probing depth (PD) of 5 to 7 mm and gingival index (GI) of >= 2. The test group received scaling and root planing (SRP) and probiotic-containing lozenges. The control group received SRP and placebo lozenges. Plaque index (PI), GI, bleeding on probing (BOP), PD, and attachment gain were measured. Gingival crevicular fluid (GCF) was sampled for the analysis of matrix metalloproteinase (MMP)-8 and tissue inhibitor of metalloproteinase (TIMP)-1 by enzyme-linked immunosorbent assay. All evaluations were performed at baseline and on days 21, 90, 180, and 360. Results: Differences in intergroup comparisons of PI, GI, BOP, and PD were found to be significant (P < 0.05) in favor of the test group at all time points. Decreased GCF MMP-8 levels and increased TIMP-1 levels were found to be significant up to day 180 (P < 0.05). Mean values of attachment gain were significantly higher in the test group compared with the control group on days 90, 180, and 360. Conclusions: Lozenges containing L. reuteri may be a useful supplement in moderately deep pockets of patients with CP. Low MMP-8 and high TIMP-1 levels may indicate the role of the lozenges in reduction of inflammation-associated markers up to day 180.
Keywords: Chronic periodontitis; dental scaling; gingival crevicular fluid; matrix metalloproteinase 8; probiotics; tissue inhibitor of metalloproteinase 1; GINGIVAL CREVICULAR FLUID; MATRIX METALLOPROTEINASE-8 LEVELS; TISSUE INHIBITORS; PROBIOTICS; COLLAGENASE; TABLETS; TIMP-1; CELLS